Respuesta :

Answer:

Identity Property of Addition.

Answer:

Reason which completes the proof of step 4 is:

Identity property of addition

Step-by-step explanation:

-(a+b)+a= -b

= -a+ (-b)+a   (distributive property)

= -a+a+(-b)     (Commutative property of Addition)

= 0+ (-b)        (Additive inverse property)

= -b         (Identity property of addition)

(Identity property of addition says that if 0 is the identity element and a is any element

Then, a+0=0+a=a)

So, reason which completes the proof of step 4 is:

Identity property of addition

ACCESS MORE